Increased Attention Through Kinetic Life Aith A Level Of Concentration On Physical Education Learning: A Study In Elementary School Students - Deny Sugandi; Dewi Susilawati; Yogi Akin (JUARA : Jurnal Olahraga, 2023)
This research examines the effect of the learning model using life kinetics on increasing learning attention as seen from the concentration level of students in one of the elementary schools in Kab. Bandung. The research method used in this research is an experimental method adapted to the research objectives of wanting to know the truth of hypotheses regarding causal relationships with a Quasi-Experimental Design research design. The analysis technique in this study uses multiple classification analyses of variance, using two ways (two-way ANOVA). Two-way analysis of variance to analyze the effect of the two independent variables, namely learning models using life kinetics and conventional learning models (not using life kinetics) with attribute variables of concentration levels (high and low). Through two-way analysis of variance and statistical data analysis techniques of IBM SPSS Version 25 software, a significant increase in attendance was found in student study groups using the life kinetic learning model.